Molekulární patologie plicních karcinomů pro rutinní praxi - update 2017 - Matěj, Radoslav; Rohan, Zdeněk; Němejcová, Kristýna; Dundr, Pavel (Ceskoslovenska patologie, 2017)
The group of non-small cell lung carcinomas includes tumors that are variable at the clinical, histopathological and molecular levels. Advances in the understanding of molecular pathology of lung adenocarcinomas in particular led to changes in their histopathological classification and treatment. Patients diagnosed with lung adenocarcinoma harboring specific mutations benefit from the administration of specific targeted therapy. Analysis of EGFR gene mutations and ALK rearrangement in lung adenocarcinomas are already routinely performed and are closely related to the indication for the administration of tyrosinkinase inhibitors. Besides EGFR mutations and ALK rearrangement there are also available other potential markers for analyzing, e.g. b-raf - BRAF, ROS1. Moreover, immunotherapy needs standardization of detection of crucial molecules, namely PD-L1. The aim of this review is to summarize the role of the most relevant molecules that could also serve as the therapeutic target for practicing pathologists.
Keywords: Protein-Tyrosine Kinases; Carcinoma, Non-Small-Cell Lung; tyrosinkinasy; Lung Neoplasms; Pathology, Molecular; Proto-Oncogene Proteins; nádory plic; nemalobuněčný karcinom plic; adenokarcinom; mutace; Humans; Mutation; NSCLC - lung adenocarcinoma - EGFR - ALK - BRAF - KRAS - RET - MET - PD-L1 - ROS1.; Adenocarcinoma; molekulární patologie; lidé; protoonkogenní proteiny